Romance Formula in Zoulfa Katouh’s Novel As Long As The Lemon Trees Grow - Alya Rizkyane Machmuri; Yuyun Nurulaen; Pepen Priyawan (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Romance formula is one of the genres that we often encounter around us. The novel As Long as the Lemon Trees Grow by Zoulfa Katouh is one of the novels that represent a romance formula. This research aims to analyze the romance formula in Zoulfa Katouh's As Long as the Lemon Trees Grow and to determine how the novel conforms to Janice A. Radway's theory of the ideal romance narrative structure. This research uses a qualitative approach with narrative analysis to examine the novel's conformity to Radway's 13 functions of the ideal romance. The result of this research shows that the novel As Long as the Lemon Trees Grow fulfills 13 functions of ideal romance, according to Janice A. Radway. The findings demonstrate how the characters’ emotional journeys and the narrative progression align with Radway's theoretical framework. Additionally, the research highlights the cultural and social dynamics embedded in the romance formula, offering insight into how it reflects broader societal themes. This study contributes to a deeper understanding of the adaptability and relevance of the romance genre in contemporary literature.